Stimulation of Rabbit Squamous Epidermis Cells Using Extracts of Mistletoe Dendrophthoe pentandra L. Miq in a Topical Gel - Lazuardi Mochamad; Chi-Hsien Chien; Jie-Long He; Eka Pramyrtha Hestianah; Hani Plumeriastuti (Veterinary Medicine International)
Quercetin-like compounds (QLCs) are secondary metabolite compounds of flavonol found in the leaf extract from the mistletoe Dendrophthoe pentandra L. Miq. This study aims to determine the ability of QLC to stimulate epithelialization in rabbit skin. The leaves were macerated with methanol, ethyl acetate, and n-hexane solvents, and crude macerates were separated and purified into QLC using preparative high-performance liquid chromatography. The purified QLC as an analyte was prepared in serial concentrations of 4.5%, 6%, 8%, and 10% and then formulated by new methods as topical gel preparations. The epithelialization stimulation test was performed on 60 rabbits divided into 20 rabbits for the trial group, the other 20 rabbits for the positive control group, and negative control groups. The trial group was split into 4 trial subgroups for topical gel application at each concentration. Gels were topically applied to the exfoliated skin of rabbits in the trial group twice a day for 5 days. The probit analysis showed that an epithelialization of 25%, 50%, and 75% of the in vivo study endpoint was found at a QLC concentration of 4.644%, 5.185%, and 5.790%. Rectangular cuboidal QLC particles with an average size of 0.01 μm–0.1 μm have shown the ability to stimulate epidermal epithelial proliferation starting from a concentration of 4.5% in topical gels with new formulations that can boost the epithelialization of the upper layers of the skin (p<0.05).